An analysis on newly introduced English verb in Oxford English Dictionary in 2016-2018: Levin's taxonomy of verb classification and verbnet / Kamilah Zainuddin and Noor Asmaa' Hussein - Zainuddin, Kamilah; Hussein, Noor Asmaa' (Universiti Teknologi MARA, 2021)
Levin (1993) argues that the behavior of verbs is determined by word meaning which is directly linked to the expression and interpretation of its argument. Based on this statement, Levin classified verbs into 48 classes and Verb Net, an English verb lexicon was created based on the extension of Levin's taxonomy of verb classification (VC). Therefore, this study presents the classification of the updated English verbs of 2016 to 2018 in the online version of the Oxford English Dictionary (OED) to examine the relevance of Levin's VC and Verb Net in the recently added repertoire of verbs. In Addition, the study seeks to find out the new verb classes introduced in this study. This study uses a mixed method to identify and classify the verbs. To conclude, this study found that both classifications were applicable and relevant in 14 new main verb classes introduced to classify the verbs that did not belong to Levin's VC and Verb Net. Hence, this contributes to the body of knowledge as the newly introduced verb classes could be used based on the given semantic and syntactic conditions.